So Distant or/and So Close? The Image of Czechs in the Perception of Polish Teachers - Anna Szafrańska (Maria Curie-Skłodowska University, Lublin, Poland, 2018)
Since joining the Schengen Area by Poland and the Czech Republic, their inhabitants have had the right to free moving. Undoubtedly, the location in the borderland is beneficial, due to the possibilities of implementing joint undertakings, which result e.g. from transfrontier agreements and the participation in some projects addressed to the residents of the countries divided/joint by the border. Borderland residence is favourable for establishing direct contacts with neighbours. In the presented study, some questions are raised concerning the knowledge the teachers living in the borderland have about their neighbours and the way in which the neighbours are described by them. The choice of teachers as the examined sample was purposeful, as they have the possibility to shape the neighbours' image of their learners. Either in a conscious way or not, they can pass down the stereotypical image which they have, or the opposite - present the knowledge and image which will encourage learners to contacts with Czechs. Associations, stereotypes and prejudices largely determine the attitude to other nations and the way of undertaking actions. This is particularly important in the situation when the respondents can shape similar attitudes of other people - in this case, their learners.